anonymous
  • anonymous
I need help to solve this dy/dx=xy+x-2y-2 // y(0)=2 thank you
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Hi tonijv, This is a separable equation. Factorize the right-hand side to see,\[y(x-2)+(x-2)=(y+1)(x-2)\]You then have,\[\frac{dy}{y+1}=(x-2)dx \rightarrow \int\limits_{}^{} \frac{dy}{y+1}=\int\limits_{}^{}(x-2)dx\]
anonymous
  • anonymous
\[\ln(y+1)=\frac{x^2}{2}-2x+c \rightarrow y=e^{\frac{x^2}{2}-2x+c}-1\]That is,\[y=Ae^{\frac{x^2}{2}-2x}-1\]Using the boundary condition,\[y(0)=Ae^0-1=2\rightarrow A=3\]
anonymous
  • anonymous
Your equation is then,\[y=3e^{\frac{x^2}{2}-2x}\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
The previous comment was correct. This is a separable equation and wanted to also note a slightly different way of factorizing the RHS: \[dy/dx = xy + x - 2y - 2 = x(y + 1) - 2(y+1) = (y+1) (x-2)\] Now place all of the y variables to one side and all of the x variables to the other and you obtain the integral that lokisan noted above. Upon solving this integral you should get: \[\ln \left| y+1 \right|=x ^{2}/2 - 2x + C\] Now plug in the initial value conditions for x = 0 and y = 1 and solve for C to obtain: \[C=\ln(2)\] Thereby, making your final answer: \[ \ln \left| y+1 \right|=x ^{2}/2 - 2x + \ln(2)\]
anonymous
  • anonymous
thanks guys is my first time here. I am lost in differentials. greetings from Barcelona
anonymous
  • anonymous
No probs.
anonymous
  • anonymous
I have given you the answer "implicitly" in terms of y but you can also solve this "explicitly" for y, but some professors don't mind which form you use.
anonymous
  • anonymous
\[y=(1/2)(x-4)(x)(y+1)+2\] The derivative of the right side of the above with respect to x is: \[(1/2)(x-4)(y+1)+(1/2) (x)(y+1)\] or \[x y+x-2 y-2\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.